(untitled) (Bangladesh Journal of Medical Science, 2025)
Corporate Social Responsibility (CSR) has shifted from a philanthropic activity to a strategic business practice, especially in Bangladesh’s banking sector, where it plays a crucial role in healthcare improvements. This article investigates how Bangladeshi banks have integrated CSR into their operations, aligning efforts with national health goals. Using content analysis of publications from the Bangladesh Central Bank and other sources, the study outlines the transition from basic charitable actions to more impactful CSR interventions. Under the Bangladesh Bank’s regulatory framework, banks are required to allocate a portion of profits to CSR, particularly focusing on healthcare, education, disaster relief, and environmental sustainability. The research highlights key healthcare initiatives such as infrastructure development, funding medical camps, and promoting public health awareness. Fluctuations in healthcare-related CSR spending from 2019 to 2023 are examined, showing a peak in 2021, followed by a decline due to political and economic instability. The article stresses the need for stronger oversight, strategic partnerships, and long-term healthcare investments to ensure sustainable outcomes. Recommendations include aligning CSR strategies with national health objectives, enhancing transparency, and collaborating with healthcare providers and NGOs. Further research is suggested to evaluate the direct impact of these initiatives on healthcare outcomes to ensure long-term effectiveness. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 67-73